Pendampingan Pelatihan Penggunaan Canva Dalam Inovasi Baru Pembelajaran Siswa - Suharti Siradjuddin; Reni Safitri; Frisca Oktaviany; Delvia; Hesti Oktaviana (Yayasan Habiburrahman Jamalu Bina Ummat, 2024)
This community service activity aims to increase creativity and new innovations in the teaching and learning process as well as to help develop students' digital skills. The method used is mentoring through several stages of activities, namely: 1) coordinating with the fifth-grade homeroom teacher and the principal of SDN 250 Maroanging to provide assistance in training on the use of Canva, 2) Explain the aims and objectives of providing assistance training on the use of Canva, 3) Present Canva material and teach students how to use the Canva application. 4) provide feedback to the participants with the aim of finding out to what extent the participants understand the procedures for using the Canva application as a learning medium. The partners for this PKM activity are fifth-grade students at SDN 250 Maroanging, numbering around 20 people. The evaluation was carried out to see the extent of participants' understanding and skills in using the Canva application and its impact on the learning process in the classroom. The results of the PKM implementation show that after participating in training assistance activities on using Canva, the training participants have succeeded in creating learning media such as infographics, powerpoints and learning videos. The outcome of this activity is that students as training participants have the knowledge and ability to create media via Canva. Furthermore, most students immediately committed to using the Canva application in the learning process and utilised it as an interesting digital learning media.